Determination of thermal response factors of building wall in Viet Nam condition based on frequency domain regression Method - Le , Minh Nhựt (Journal of Technical Education Science, 2016)
The objective of this research is to determine the thermal response factors of building wall to use for thermal load calculation of building in Viet Nam condition. In this work, a MATLAB program was developed based on the frequency domain regression (FDR) method to estimate the polynomial s-transfer function of transient heat conduction of building wall. The values of thermal response factors were obtained by applying Laplace transforms on the polynomial s-transfer function. The calculated results showed that the fifth-order polynomial s-transfer functions of the outside heat conduction GX(s), across heat conduction GY(s) and inside heat conduction GZ(s) of building wall were found at the 55 first points of N=11×(7-2)+1 frequency points within the frequency range of 10-7 to 10-2 radian.s-1, and the error percentage between the thermal transmittance coefficient U and the sum of thermal response factors of the outside heat conduction, across heat conduction and inside heat conduction of the building wall were 7.44×10-9%, 5.83×10-9%, 5.86×10-9%, respectively.